Évaluer le degré de mobilité des rennes paléolithiques à partir de l’étude ostéométrique de métacarpiens - Galán López, Ana Belén; Costamagno, Sandrine; Burke, Ariane (CCSD, 2021)
International audience Paleolithic reindeer (Rangifer tarandus) played an importantrole in the life of human populations in western and centralEurope during much of the Paleolithic period. In the South-Westof France and in particular during the Magdalenian, reindeerfrequently were the privileged prey of hunter-gatherer groups.However, and despite numerous attempts to reconstruct themigratory behavior of Paleolithic reindeer, there is no agreementon the range of movement of this prey. Modern ethologicaldata indicate that reindeer herds adopted different migrationstrategies depending on the type of habitat and the topographyof the environment. Thus, the Emorph project aims to researchmorphometric criteria using cutting-edge methodologies, suchas Machine Learning, to identify the extent of reindeer migrations.Based initially on the study of modern Caribou populationswith distinct migratory behaviors, the results obtained could beapplied to several Magdalenian assemblages from southwesternFrance in the future, with the goal of reconstructing the routes ofthese tardiglacial reindeer. Le Renne (Rangifer tarandus) a joué un rôle important pour lespopulations humaines en Europe occidentale et centrale durantune grande partie de la période paléolithique. Dans le Sud-Ouestde la France (notamment au Magdalénien), le Renne figure fréquemmentparmi les proies privilégiées des groupes de chasseurs-cueilleurs. Malgré les nombreuses tentatives de reconstitutiondu comportement migratoire des rennes paléolithiques, il n’existepas de consensus quant à son degré de mobilité. Les donnéeséthologiques modernes indiquent que les troupeaux de rennesadoptent différentes stratégies de mobilité en fonction du typed’habitat et de la topographie. Le projet Emorph vise à rechercherdes critères morphométriques, en combinaison avec destechniques d´apprentissage automatique, permettant d’identifierl’étendue des migrations du Renne. Fondés sur l’étude de populationsde caribous modernes aux comportements migratoiresdistincts, les résultats ...